Zróżnicowanie ekstensji tekstowej fonetycznych form obocznych w Księgach o gospodarstwie Piotra Krescentyna z 1549 roku - Osiewicz, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The article is a continuation of studies concerning textual differences in distribution of variant phonetic forms. The analysis covers the forms being a part of four variances: jestli // jesli, -mdl- // -mgl-, miedzy // między and -mieszk- // -mięszk-. Different textual distribution of the studied forms proved to be significant – not only revealed the segmentation of text known from previous analysis (graphical and phonetic), but also 3 new, previously unknown text boundaries extending between the columns 510/511, 591/592 and 612/613. The strongest relationship with the job of a compositor is indicated by textual repartition of forms belonging to two variances: miedzy // między i jestli // jesli. With regard to the analysed forms the central part Cresc is most standardized, contained in the columns 138-384, whereas the most progressive (containing the greatest number of progressive variants) – is the section of text including the columns 381a–R10v. The completed study has also demonstrated that the boundary between the cluster Q and R established by Kazimierz Piekarski on the basis of a typographical analysis is also the boundary of occurrence of certain phonetic phenomena.